(untitled) (Latakia University (formerly Tishreen)Journal for Research and Scientific Studies - Economic and Legal Sciences Series, 2026)
Fluctuations in the value of currency are among the most prominent problems that have significantly impacted the stability of financial transactions and the settlement of debts, especially in light of the economic crises, political unrest, and rapid monetary changes witnessed in the Arab world. Currency, once a stable standard of exchange and valuation, has in many cases become unable to perform this role with the same efficiency, resulting in profound effects on financial obligations and civil contracts. This research examines the causes of currency fluctuations, starting with domestic economic policies, moving on to external factors, the impact of this on exchange rate volatility, the correlation of foreign currencies, and finally, political crises and wars. In addition, the opinions and analyses of Muslim jurists, which have played a significant role in enriching this research, are also discussed. The legal position on this phenomenon is also examined, with a particular focus on Syrian law, and brief comparisons are made with a number of Arab legislations that have addressed this challenge with varying degrees of clarity and organization. At the end of the research, some special legal applications that deviated from the general rules approved by the legislator in the rule of debt settlement were addressed, as the Syrian legislator established some special texts to mitigate the impact of economic fluctuations on contracting parties.